Implementation of the FIFO System and Its Impact on Asset Stock Accuracy at the Nias Regency Statistics Office - Waruwu, Candry Yurlina; Telaumbanua, Rina Novianti; Zega, Agusniaman; Zega, Osadikman; Waruwu, Jurisman; Zai, Arliyanto (Universitas Mohammad Husni Thamrin, 2025)
State Property (BMN) is a crucial asset that supports the operations of government agencies and reflects state assets that must be managed in an orderly, efficient, and accountable manner. BMN management encompasses recording, maintenance, data updating, and reporting, which require a fast, accurate, and easily accessible information system. In response to these challenges, this study aims to implement a web-based BMN recording and updating system using the FIFO (First In, First Out) method. This system is expected to improve recording accuracy, accelerate reporting, and support digital transformation in asset management within the Nias Regency Statistics Agency (BPS). Implementing the FIFO (First In, First Out) system is a strategic step to improve the accuracy of asset stock recording at the Nias Regency Statistics Agency (BPS) Office. Previously, manual spreadsheet-based asset management led to the risk of recording errors, reporting delays, and a lack of efficiency. This study aims to develop and implement a web-based system that supports the FIFO method to improve the accuracy and efficiency of asset stock management. Research data was collected through observation, interviews, and document analysis, using a waterfall software development approach. The results showed that implementing the FIFO system improved stock accuracy by up to 95%, accelerated the audit process, and simplified reporting. Further development, such as integration with cloud technology and mobile applications, is recommended to support sustainable and efficient asset management within the Nias Regency BPS.